Medication regimen complexity and medication adherence in elderly patients with chronic kidney disease. Issue 3 (19th February 2019) - Parker, Krystina; Bull‐Engelstad, Ingrid; Aasebø, Willy; von der Lippe, Nanna; Reier‐Nilsen, Morten; Os, Ingrid; Stavem, Knut
Abstract: Introduction: Elderly patients with chronic kidney disease (CKD) stage 5 with or without dialysis treatment usually have concomitant comorbidities, which often result in multiple pharmacological therapies. This study aimed to identify factors associated with medication complexity and medication adherence, as well as the association between medication complexity and medication adherence, in elderly patients with CKD. Methods: This prospective study involved elderly patients with CKD stage 5 (estimated glomerular filtration rate < 15 ml/min/1.73m 2 ) recruited from three Norwegian hospitals. Most of the patients were receiving either hemodialysis or peritoneal dialysis. We used the Medication Regimen Complexity Index (MRCI) to assess the complexity of medication regimens, and the eight‐item Morisky Medication Adherence Scale (MMAS‐8) to assess medication adherence. Factors associated with the MRCI and MMAS‐8 score were determined using either multivariable linear or ordinal logistic regression analysis. Findings: In total, 157 patients aged 76 ± 7.2 years (mean ± SD) were included in the analysis. Their overall MRCI score was 22.8 ± 7.7. In multivariable linear regression analyses, female sex (P = 0.044), Charlson Comorbidity Index of 4 or 5 (P = 0.029) and using several categories of phosphate binders (P < 0.001 to 0.04) were associated with the MRCI. Moderate or high adherence (MMAS‐8 score ≥ 6) was demonstrated by 83% of the patients. The multivariable logistic regression analyses found no association of medication complexity, age or other variables with medication adherence as assessed using the MMAS‐8. Discussion: Female sex, comorbidity and use of phosphate binders were associated with more‐complex medication regimens in this population. No association was found between medication regimen complexity, phosphate binders or age and medication adherence. These findings are based on a homogeneous elderly group, and so future studies should test if they can be generalized to patients of all ages with CKD.